The Effect of Resilient Supply Chains on Sustainable Trade in Sri Lanka's Export Sector in a VUCA World - Herath, C.; Fernando, M.T.; Pramudika, H. (Faculty of Management Studies and Commerce University of Sri Jayewardenepura, 2024)
Sustainable trading practices in Sri Lanka's export sector are examined in this study considering the current VUCA conditions, which are characterized by volatility, uncertainty, complexity, and ambiguity. The major objective is to determine the impact of Vulnerabilities, Capabilities, Strategies, and Performance indicators on sustainable trade in a resilient supply chain. A thorough methodology including a literature review, primary data collecting through questionnaires, and advanced statistical analysis are utilised in the research. To comprehend the relationship between sustainable commerce and resilient supply chains in a volatile, uncertain, complex, and ambiguous (VUCA) environment, the literature review lays the empirical framework. A robust supply chain structure is required for long-term trade sustainability since it reveals the complex dynamics and difficulties encountered by the export ector. To collect primary data, a structured questionnaire was given to 198 people in Colombo who work for Sri Lankan export companies, supply chain experts and professionals, and international trade partners and organisations. Using IBM SPSS, we conduct thorough analyses on the data, evaluating for reliability, analysing correlations, and using regression to draw conclusions. A fascinating tale emerges from the analysis. Except for "capability," all the independent variables pertaining to resilient supply chains have a statistically significant effect on the dependent variable, which is sustainable commerce. This highlights how important it is to strengthen sustainable trade practices in Sri Lanka's export sector by addressing supply chain resilience. This study offers practical insights for practitioners and policymakers as well as academics who are trying to understand the relationship between volatile, uncertain, complex, and volatile (VUCA) environments, resilient supply chains, and sustainable commerce. The results highlight the importance of stakeholders making improvements to supply chain performance indicators, strategic adaptation, and vulnerabilities management a top priority to successfully navigate the obstacles caused by VUCA dynamics. Finally, in a volatile, unpredictable, complex, and ambiguous (VUCA) environment, strengthening supply chains is a strategic need for Sri Lanka's export business. Sri Lanka's export sector has been growing, and this report lays out a plan to strengthen the supply chain, create an atmosphere that encourages sustainable trading practices, and keep it going.
Keywords: Sustainable Trading Practices, Sri Lanka Export Sector, VUCA Conditions, Resilient Supply Chain, Vulnerabilities, Capabilities, Strategies, Performance Indicators